Fifth Annual International Exhibition of Miniature Art Toronto - Canada. - Metro Toronto Convention Centre, Toronto (Toronto : Del Bello Gallery, 1990)
Bugan, Zdenek ; Yoshio, Yamanobe ; Santiago, Reynaldo ; Botezatu, Pavel ; Hunter, Debby ; Tousova, Daniela ; Dimma, Katharine ; Bos, Robert ; Savulich, Andrew ; Wald, Carol ; Laporta, Eduardo Daniel ; Mitev, Emil ; etc.
Fifth Annual International Exhibition of Miniature Art Toronto - Canada, November 2 - December 30, 1990 ; Juried Show, Metro Toronto Convention Centre, Toronto, November 2-3-4, 1990
English
kunstcatalogus